Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package in India (SPRINT INDIA) study protocol. Issue 1 (January 2020) - Kate, Mahesh Pundlik; Arora, Deepti; Verma, Shweta Jain; Sylaja, PN; Renjith, Vishnu; Sharma, Meenakshi; Pandian, Jeyaraj Durai; ,
Rationale: Recurrent stroke, cardiovascular morbidity, and mortality are important causes of poor outcome in patients with index stroke. Despite the availability of best medical management recurrent stroke occur in up to 15–20% of patients with stroke in India. Education for stroke prevention could be a strategy to prevent recurrent strokes. Hypothesis: We hypothesize that a structured semi-interactive stroke prevention package can reduce the risk of recurrent strokes, acute coronary artery syndrome, and death in patients with sub-acute stroke at the end of one year. Design: Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package in INDIA (SPRINT INDIA) is a multi-center stroke trial involving 25 centers under the Indian Stroke Clinical Trial Network. Patients with first ever sub-acute stroke within two days to three months of onset, age 18–85 years, mRS <5, showing recent stroke in imaging are included. Participants or caregivers able to read and complete tasks suggested in a stroke prevention workbook and have a cellular device for receiving short message service and watching videos. A total of 5830 stroke patients speaking 11 different languages are being randomized to intervention or control arm. Patients in the intervention arm are receiving a stroke prevention workbook, regular educational short messages, and videos. All patients in the control arm are receiving standard of care management. Summary: Structured semi-interactive stroke prevention package may reduce the risk of recurrent strokes, acute coronary artery syndrome, and death in patients with sub-acute stroke. Trial registration: This trial is registered with clinicaltrials.gov (NCT03228979) and CTRI (Clinical Trial Registry India; CTRI/2017/09/009600).